Turbulence and thermo‐flow behavior of air in a rectangular channel with partially inclined baffles. Issue 9 (1st July 2022) - Salhi, Jamal‐Eddine; Mousavi Ajarostaghi, Seyed Soheil; Zarrouk, Tarik; Saffari Pour, Mohsen; Salhi, Najim; Salhi, Merzouki
Abstract: In this paper, the thermal performance improvements of a heat removal system like an electronic system have been analyzed. The studied case is a horizontal channel in which two partially inclined baffles are attached with variable height and number. The channel is crossed by a forced convective flow of a cooling fluid (air). This numerical work evaluates the influences of the height and number of the baffles on the enhancement of the heat transfer rate. The mathematical model of this system is composed of nonlinear partial equations that the analytical solution for them is very complex, hence the need for numerical analysis is mandatory with the aid of a finite volume method. Accordingly, The numerical results are presented in axial and transverse velocity, temperature, local and average Nusselt number, local friction coefficient, pressure drop, heat transfer rate, and turbulence kinetic energy. The results revealed that it is possible to improve the thermal performance of the considered system by adopting designs that allow the maximum heat transfer rate with the minimum energy loss. In addition, results show that at the lowest Reynolds number (Re = 10, 000), as the height of baffles rises from 0.01 to 0.03 m (growth by 200%), the heat transfer rate augments about 59.09%. Moreover, at the highest evaluated Reynolds number (Re = 87, 300), by increasing the height of baffles up to 200%, the heat transfer rate increases by approximately 50.53%. Furthermore, employing a higher number of baffles leads to more heat transfer rates and a significant pressure drop. Abstract : In this study, the turbulence heat transfer, and fluid flow in an air channel equipped with partially inclined baffles is evaluated numerically. This study consists of two sections, in the first part, the impact of the height of the baffles, and in the next one, the impact of the number of baffles on the thermal behavior of fluid flow is examined.